2020
DOI: 10.7202/1071948ar
|View full text |Cite
|
Sign up to set email alerts
|

Archaeologies of Climate Change: Perceptions and Prospects

Abstract: Ce document est protégé par la loi sur le droit d'auteur. L'utilisation des services d'Érudit (y compris la reproduction) est assujettie à sa politique d'utilisation que vous pouvez consulter en ligne.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 100 publications
0
4
0
Order By: Relevance
“…Most of the studies reported on proactive adaptation planning which is focusing on a decision‐making process that can reduce climate change impacts before the impacts are further observed (in the future). Specifically, the studies emphasized the need for increased research on climate change risks and impacts to ICH (Blanchette et al, 2021; Britton & Hillerdal, 2019; Flyen et al, 2020; Hollesen et al, 2018), monitoring of climate stressors on ICH (Holmgaard et al, 2019; Pearson et al, 2010), integration of community perceptions and knowledge in development of proactive adaptation actions (Bertulli et al, 2013; Britton & Hillerdal, 2019; Jensen, 2020; Tran et al, 2021), and the need for the development of approaches and methods to deal with irreversible loss of Arctic heritage (Jensen, 2020). Other studies called for designing and implementing targeted policy mechanisms, laws and regulations for climate change adaptation and protection of polar heritage (B. W. Barr, 2017; S. Barr, 2019; Pearson et al, 2010; Viikari, 2009), including transparent prioritization decision‐making processes for diverse ICH (B. W. Barr, 2017; Jensen, 2020).…”
Section: Impacts Of Climate Change On Immovable Cultural Heritage In ...mentioning
confidence: 99%
“…Most of the studies reported on proactive adaptation planning which is focusing on a decision‐making process that can reduce climate change impacts before the impacts are further observed (in the future). Specifically, the studies emphasized the need for increased research on climate change risks and impacts to ICH (Blanchette et al, 2021; Britton & Hillerdal, 2019; Flyen et al, 2020; Hollesen et al, 2018), monitoring of climate stressors on ICH (Holmgaard et al, 2019; Pearson et al, 2010), integration of community perceptions and knowledge in development of proactive adaptation actions (Bertulli et al, 2013; Britton & Hillerdal, 2019; Jensen, 2020; Tran et al, 2021), and the need for the development of approaches and methods to deal with irreversible loss of Arctic heritage (Jensen, 2020). Other studies called for designing and implementing targeted policy mechanisms, laws and regulations for climate change adaptation and protection of polar heritage (B. W. Barr, 2017; S. Barr, 2019; Pearson et al, 2010; Viikari, 2009), including transparent prioritization decision‐making processes for diverse ICH (B. W. Barr, 2017; Jensen, 2020).…”
Section: Impacts Of Climate Change On Immovable Cultural Heritage In ...mentioning
confidence: 99%
“…There is, therefore, an urgent need for new techniques to capture vast swathes of the landscape quickly, remotely and relatively inexpensively, especially given the danger posed to cultural sites by accelerated coastal erosion and rising sea levels (Britton & Hillerdal, 2019). Here, the use of remote sensing is suitable for this purpose given its proven ability to expediently survey large areas of inaccessible terrain without the immediate need for costly ground surveys (Cerra et al, 2016;Linares-Matás & Lim, 2021;Parcak, 2009).…”
Section: Collaborative Remote Sensing and Ethnoarchaeological Approaches For Understanding Cultural Landscapes In Southwest Alaskamentioning
confidence: 99%
“…Remote sensing may also be used to help document and assess erosion risk to known cultural sites using visual inspection and automated analytical processes. Landscape change is a source of considerable cultural anxiety in the Y-K Delta (Britton & Hillerdal, 2019;Cusack-McVeigh, 2017), and such studies help Yup'ik community members visualize the impact and scope of significant erosion events near traditional places associated with Yuuyaraq along the Bering Sea. For instance, the following automated change detection process was which is has been shown to be more effective in grassland archaeological landscape contexts under certain conditions (Bennett et al, 2012).…”
Section: Remote Sensing For Identifying Vulnerable Cultural Sitesmentioning
confidence: 99%
“…In an era of unprecedented climate change, however, such changes pose an immediate, existential threat to the Alaskan Native Yup'ik people (pl. Yupiit) who have called this landscape home for the past 1500 years [2][3][4][5][6]. In particular, the reduction of permafrost levels and sea-ice along the Bering Sea coast, when combined with increased frequency and intensity of coastal storms, has led to the rapid degradation of coastlines and waterways [1,7].…”
Section: Introduction 1landscapes In Flux and Heritage At Riskmentioning
confidence: 99%